2010
DOI: 10.1175/2010jcli3429.1
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Shift in El Niño Influences on Indo–Western Pacific and East Asian Climate in the 1970s*

Abstract: El Niñ o's influence on the subtropical northwest (NW) Pacific climate increased after the climate regime shift of the 1970s. This is manifested in well-organized atmospheric anomalies of suppressed convection and a surface anticyclone during the summer (June-August) of the El Niñ o decay year [JJA(1)], a season when equatorial Pacific sea surface temperature (SST) anomalies have dissipated. In situ observations and oceanatmospheric reanalyses are used to investigate mechanisms for the interdecadal change. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
195
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(207 citation statements)
references
References 82 publications
11
195
0
1
Order By: Relevance
“…IOD events have cooccurred with El Niño more frequently after the mid-1970s climate shift [e.g., Chakravorty et al, 2014]. Recent studies have revealed that after the mid-1970s climate shift, the ocean dynamics have acted as a major driver in modulating the sea surface temperature (SST) at interannual time scale mainly over the equatorial eastern Indian Ocean (EIO) and southern TIO (STIO) [Xie et al, 2010;Chakravorty et al, 2014]. In particular, SST variability in the southwestern TIO is closely associated with the westward propagating Rossby waves partly generated by the El Niño-induced anticyclonic wind stress curl in the eastern basin Kinter, 2001, 2002;Xie et al, 2002;Chowdary et al, 2009;Schott et al, 2009;Gnanaseelan and Vaid, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…IOD events have cooccurred with El Niño more frequently after the mid-1970s climate shift [e.g., Chakravorty et al, 2014]. Recent studies have revealed that after the mid-1970s climate shift, the ocean dynamics have acted as a major driver in modulating the sea surface temperature (SST) at interannual time scale mainly over the equatorial eastern Indian Ocean (EIO) and southern TIO (STIO) [Xie et al, 2010;Chakravorty et al, 2014]. In particular, SST variability in the southwestern TIO is closely associated with the westward propagating Rossby waves partly generated by the El Niño-induced anticyclonic wind stress curl in the eastern basin Kinter, 2001, 2002;Xie et al, 2002;Chowdary et al, 2009;Schott et al, 2009;Gnanaseelan and Vaid, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term IOB SST warming has commonly been attributed to the anthropogenic effect associated with global warming [Barnett et al, 2005;Pierce et al, 2006]. Nevertheless, decadal changes over the Indian Ocean have been found closely related to ENSO [Cole et al, 2000;Allan et al, 1995;Reason et al, 2000;Xie et al, 2010;Chowdary et al, 2012]. For example, Allan et al [1995] suggested that the epochal changes in the mean condition over the south Indian Ocean are in-phase with ENSO-related correlation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the thermocline shoaling in the southwest TIO and the strengthening of ENSO intensity, interannual variability of TIO SST is intensified after the late 1970s Xie et al, 2010). During this epoch, the TIO warms in response to El Niño, and this warming then influences the climate in the Indian Ocean (IO) and surrounding regions after El Niño decays (Yang et al, 2007;Xie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%